Marriage and the City - Pieter A. Gautier; Michael Svarer; Coen N. Teulings (Tinbergen Institute, 2005)
Do people move to cities because of marriage market considerations? In citiessingles can meet more potential partners than in rural areas. Singles are thereforeprepared to pay a premium in terms of higher housing prices. Once married, themarriage market benefits disappear while the housing premium remains. We extendthe model of Burdett and Coles (1997) with a distinction between efficient (cities)and less efficient (non-cities) search markets. One implication of the model is thatsingles are more likely to move from rural areas to cities while married couples aremore likely to make the reverse movement. A second prediction of the model is thatattractive singles benefit most from a dense market (i.e. from being choosy). Thosepredictions are tested with a unique Danish dataset.
Keywords: J12; J64; 330; Marriage; search; mobility; city; Wohnungswechsel; Landflucht; Suchtheorie; Ehe